Commitment to sustainability in a Brazilian technological university: a case study - Scur, Gabriela; Alliprandini, Dario (Administração: Ensino e Pesquisa, 2023)
Higher education institutions have been steadily integrating sustainable practices into their operations. Despite these efforts in the implementation, several challenges must be overcome to achieve sustainability. There is a lack of studies that investigate sustainable development in higher education, and the efforts of a small, specialized university have been scarcely analyzed in detail. This manuscript addresses the path toward sustainability followed by a private Brazilian technological university. The university in São Paulo is one of the region’s most traditional and oldest universities, focused on engineering, computing, and business. Data from 2019/2020 on energy and water consumption and solid waste generation for the university campus were discussed and benchmarked with GreenMetric indicators. The data was analyzed by a theoretical framework composed of 6 dimensions. Challenges were identified, and remedial actions were proposed to transform the university into a greener campus. Even during the COVID-19 pandemic, the higher education institution kept sustainability projects active, some of which received international awards. However, this study reveals that although sustainable development is considered very important to HEI and society, it is not yet embedded in the system’s strategies, activities, and policies.